Exploring Organizational Factors, Academic Fraud Behaviors, and Academic Integrity of Accounting Students - Muhamad Arief Ramdhany; Arvian Triantoro; Raden Dian Hardiana; Hari Mulyadi (Jurnal ASET (Akuntansi Riset), 2023)
Main Purpose - The research objectives are to examine the relationship between organizational factors and academic fraud behaviors, to investigate the relationship between academic fraud behaviors and academic integrity, and to identify the most effective strategies for promoting academic integrity and preventing academic fraud behaviors among accounting education students in the university.Method - The research used a cross-sectional survey that collected data from 104 students of accounting education study program as population who have attended the course ‘Accounting Information System’, and using random sampling, 82 students participated. The data were collected using structured questionnaires that measured the study's constructs. Partial Least Square (PLS) was used to analyze the quantitative data.Main Findings - Organizational factors have a significant negative effect on academic fraud behaviors. Academic fraud behaviors have a significant negative effect on academic integrity. Organizational factors have a direct and an indirect effect on academic integrity through academic fraud behaviors.Theory and Practical Implications - The finding could have important implications for the university as an educational institution seeking to prevent or address academic misconduct by focusing on improving its organizational factors. The solid organizational factors of the university can mainly prevent academic fraud behaviors for students and teaching staff, leading to acceptable academic integrity for the students and teaching staff. Novelty - This study provides novel insights into the relationship between organizational factors, academic fraud behaviors, and academic integrity in the context of accounting education students in higher education.